1993
DOI: 10.1590/s0037-86821993000400008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopatia chagásica crônica causando insuficiência cardíaca congestiva na infância: estudo clínico e histopatológico de um caso, com ênfase para as lesões dos sistemas excito-condutor e nervoso autônomo intracardíaco

Abstract: São incomuns as referências à fase crônica da doença de Chagas (DC) na infância e adolescência e particularmente raras as descrições da anatomia patológica da cardiopatia chagásica crônica (CChCr) na primeira década. Ao que nos consta, somente três trabalhos5 8 24 relatam as alterações morfológicas da CChCr no primeiro decênio de vida. Nenhum deles aborda o estudo microscópico do sistema excito-condutor e só Tafiiri e cols.24 realizaram estudo morfológico do sistema nervoso autônomo intracardíaco (SNAIC). Tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In paediatric patients with Chagas disease, clinical and echocardiographic alterations are infrequent, even in untreated patients. 28 A large retrospective study performed in Brazil that included all medical records obtained at a University Hospital between 1965 and 1984 and more than 18000 autopsies, revealed 19 Chagas disease patients under 18 years old with positive serology and findings compatible with chronic Chagasic heart disease. 29 In a seroepidemiological study performed in México, where more than 3000 untreated individuals younger than 18 years old living in a risk area were tested, Salazar-Schettino et al found 14 paediatric patients with septal and/or wall hypertrophy, ejection fraction below 57% and increased systolic pulmonary artery pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In paediatric patients with Chagas disease, clinical and echocardiographic alterations are infrequent, even in untreated patients. 28 A large retrospective study performed in Brazil that included all medical records obtained at a University Hospital between 1965 and 1984 and more than 18000 autopsies, revealed 19 Chagas disease patients under 18 years old with positive serology and findings compatible with chronic Chagasic heart disease. 29 In a seroepidemiological study performed in México, where more than 3000 untreated individuals younger than 18 years old living in a risk area were tested, Salazar-Schettino et al found 14 paediatric patients with septal and/or wall hypertrophy, ejection fraction below 57% and increased systolic pulmonary artery pressure.…”
Section: Discussionmentioning
confidence: 99%